PERSONALITY TRAITS AND ORGANIZATIONAL SUPPORT AS PREDICTORS OF WORK-LIFE BALANCE AMONG SHOPRITE WORKERS - Emmanuel Etim Uye; Victoria A. John; David E Okurame (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2024)
Personality traits and organizational support as predictors of work-life balance among shoprite workers. Work-life balance has become an emerging issue where bothorganization and   employees tend to benefit. However no consistent results have been obtained using different predictors. Therefore, this study investigated personality traits and organizational support as predictors of work-life balance among workers in Shoprite in Ibadan metropolis. The study adopted a cross-sectional survey design while purposive sampling technique was used to select one superstore: Shoprite in Ibadan. Data were collected from 200 participants using three validated scales and analyzed using t-test of independent samples and multiple regressions analysis. Three hypotheses were tested and accepted at a p < 0.05 level of significance. The result indicated that perceived organizational support significantly influenced work-life balance [t (198) = 2.12, p <..05] among study participants. Also, the result revealed that personality traits of extraversion, agreeableness, conscientiousness, neuroticism and openness to experience jointly predicted work-life balance among workers (R2 = 0.04, F (5, 191) = 1.64, p < 0.05). Furthermore, personality traits and organizational support jointly predicted work-life balance among study participants (R2 = 0.08, F (6,190) = 2.89, p < 0.05). However, only perceived organizational support independently predicted work-life balance. The study concluded that personality traits and organizational support are good predictors of work-life balance among study participants. It is recommended that workers should learn self-and time-management techniques to achieve maximum